Cytokine Biomarkers Associated with Human Extra-Pulmonary Tuberculosis Clinical Strains and Symptoms - Ranaivomanana, Paulo; Raberahona, Mihaja; Rabarioelina, Sedera; Borella, Ysé; Machado, Alice; Randria, Mamy J. De Dieu; Rakotoarivelo, Rivo A.; Rasolofo, Voahangy; Rakotosamimanana, Niaina (Frontiers in Microbiology, 2018)
Background The primary site of infection for M. tuberculosis (Mtb) is the alveolar macrophages. However, Mtb can disseminate into other organs and causes extrapulmonary tuberculosis (EPTB). The diagnosis of EPTB is challenging due to relatively inaccessible infectious sites that may be paucibacillary and with clinical symptoms varying by site that are similar to those seen in other diseases. Hence, we sought to identify the expression patterns of a variety of cytokines that may be specific to EPTB from in vitro infections and in the plasma of TB patients. Methods To define those cytokine secretions associated with EPTB, human THP-1 derived macrophages were first infected with Mtb clinical isolates from pulmonary and EPTB. Infected macrophages supernatants were harvested at different time points and cytokines known to play key roles in TB immune responses including TNF-α, IL-6, IL-10, IFN-γ, and VEGF-A were measured by ELISA. Those cytokines that were in vitro associated to EPTB were also measured in the plasma from patients with PTB, EPTB, non-EPTB-confirmed-like symptoms and healthy controls. Results While all of the studied cytokine secretions varied after in vitro infection, higher levels of TNF-α and VEGF secretions were observed in vitro in the infected macrophages respectively in the PTB and EPTB infecting clinical isolates. Similar trends were observed from the plasma of patients where patients with PTB showed significantly higher level of TNF-α compared to EPTB and healthy control groups. The patients with EPTB showed higher plasma level of VEGF compared to those patients with PTB (p<0.05), to the non-EPTB (p<0.01) and to healthy controls group (p<0.0001). Using Receiver Operating Curves (ROC), we showed that TNF-α and VEGF concentrations could distinguish EPTB from non-confirmed EPTB with high sensitivity and specificity. Conclusion Pulmonary and extrapulmonary Mtb clinical isolates showed different cytokine induction pattern in human macrophages that is also found in the plasma level of the EPTB patients. Further investigations are needed to define cytokine secretions that can lead to the definition of bio-signatures to differentiate EPTB from other pathologies with confusing symptoms that hampered the diagnosis of TB.